1999
DOI: 10.1023/a:1008089715153
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In recent times there has been a growing research interest in palm oil, one of the major edible plant oils in the tropical countries, because of the link between dietary fats and coronary heart disease. Obtained from a tropical plant, Elaesis guineensis, it has a polyunsaturated fatty acid/saturated fatty acid ratio close to unity and a high amount of antioxidant vitamin A precursors and vitamin E. Palm oil is consumed in the fresh state and/or at various levels of oxidation. Feeding experiments in various ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(23 citation statements)
references
References 31 publications
2
21
0
Order By: Relevance
“…The mean 1∶1 ratio of saturated to unsaturated fatty acids was in accordance with Ebong et al [14]). Our data are consistent with other reports for genetic materials descending from the La Mé origin, characterized by its relatively low amount of palmitic acid and high amount of oleic acid in comparison to other E. guineensis origins [44].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The mean 1∶1 ratio of saturated to unsaturated fatty acids was in accordance with Ebong et al [14]). Our data are consistent with other reports for genetic materials descending from the La Mé origin, characterized by its relatively low amount of palmitic acid and high amount of oleic acid in comparison to other E. guineensis origins [44].…”
Section: Discussionsupporting
confidence: 89%
“…Because of its saturated/unsaturated fat ratio close to 1 and its concentrations of carotenoids, tocopherols, and tocotrienols, palm oil is considered an oxidatively stable oil [6], [14] that has no equivalent among other vegetal oils. Another goal linked to the high oleic acid content is to improve the frying properties of palm oil for the food market, although the quality of palm oil in deep-fat frying methods has already been established [15].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathological examination of livers from t -BHP-treated rats whose diet was supplemented with rooibos and RPO revealed enhanced hepatocellular architecture with slight lymphocyte infiltration, which is a clear manifestation of the hepatoprotective effects of rooibos and RPO. This result is consistent with previous findings that have been reported in different experimental models of rats exposed to other toxicants where rooibos or RPO have been supplemented [72, 74, 92–95]. …”
Section: Discussionsupporting
confidence: 93%
“…Red palm oil is rich in cocktail of lipid soluble antioxidants such as α - and β -carotene, lycopene, tocopherols ( α , β , γ , and δ isoforms), tocotrienols ( α , β , γ , and δ isoforms) and coenzyme Q 10 [47, 73]. In vivo experiments using various animal models have revealed that RPO has many health benefits including protection against oxidative stress [44, 74], modulation of serum lipid profile [43, 44], and protection of the heart against ischaemia/reperfusion injury [4648]. …”
Section: Discussionmentioning
confidence: 99%
“…These results may be attributed to the fat content and quality of palm oil present in the diet. Palm oil in its fresh state has vitamins A and E, carotenoids, and other antioxidants which make it less injurious to the tissues when compared with the thermally oxidized form that lacks these vital complements [17]. Oxidation of palm oil leads to release of free radicals which are devastating to tissues and organs of the body [3, 6, 1721].…”
Section: Discussionmentioning
confidence: 99%